Basic Principles of Chemistry Part III :State of Matter and Thermodynamics - chemistry Part III - Fernando,J.N.Oleap (Colombo Open University, 1995)
Bachelor of Science Level 3
Keywords: chemistry -- Thermodynamics -- state of matter; OUSL